ANALISIS KAPASITAS SUNGAI MAKAK MENGGUNAKAN STANDART STEP METHOD: Makak River Capacity Analysis Using Standart Step Method - Salehudin, Salehudin; Hasyim, Hasyim (Ganec Swara, 2025)
Makak river is located in gria village, lingsar district, west lombok regency with coordinates 8033’19.7”s 116008’01.4”e. makak river is unable to drain runoff water discharge due to changes in land use, which has an impact on river capacity. the purpose of the analysis is to check river capacity against the impact of changes in widening, spillway structure, depth, slope, sedimentation and river cliffs, with a review of the simulation of return period discharge that exceeds river capacity. simulated return period floods are used to determine river capacity using the nakayasu method, gama satu and muskingum methods. the results of the nakayasu synthetic unit hydrography (hss) analysis; less than 25 years 25.52 m3/sec, 50-year return period 28,474 m3/sec, 100-year return period 31,228 m3/sec, gama method; 25-year return period 26,523 m3/sec., 50-year return period 27,641 m3/sec., 100-year return period 28,705 m3/sec., muskingum out-flow discharge 8,744 m3/sec., inflo 28,705 m3/sec. standard step method analysis; spillway cres elevation ± 29, water surface elevation at spillway ± 29.5. diversion elevation ± 30 m, intake elevation ± 28.5 cm, drain elevation ± 28.00, river widening 250 meters, bed width 8 meters, cliff height 2 meters, river slope (i) 0.0015. sedimentation of makak river of 200 tons per year is drained once in two months